Compositional Analysis of Greco-Roman Unguentaria Residues from the Michael C. Carlos Museum - Samantha J. Mahan; Renée Stein; Ruth Ann Armitage (Heritage)
Unguentaria are ancient vessels for oils, perfumes, ointments, or balms. Glass unguentaria are typically small in size and have long narrow necks to limit the loss of precious contents through spills and evaporation. The vessels may have single or double barrels. This study includes both double and single unguentaria from unprovenanced archaeological contexts. Residues found inside the vessels may reveal the original contents. Gas chromatography-mass spectrometry (GC-MS) and direct analysis in real time-mass spectrometry (DART-MS) were used to identify organic components of the residues, while headspace solid-phase microextraction (HS-SPME) gas chromatography mass spectrometry provided a method to target specifically the volatile aroma compounds. Inorganic compounds in the unguentaria residues were identified by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS). The results are consistent with a plant oil base, but few volatile perfume components could be characterized. While the collection of unguentaria may have contained perfumes, these results do not rule out the possibility of other unguents such as cosmetics.